Fast metabolism food Rx : 7 powerful prescriptions to feed your body back to health - Pomroy, Haylie; Adamson, Eve (Harmony, 2016)
"Haylie Pomroy, celebrated nutritionist, and New York Times bestselling author of The Fast Metabolism Diet shares a prescription for total health based on decades of work using food as metabolic medicine. Our bodies are always talking; we just need to learn how to listen to them. Sometimes they whisper to us--our energy is off, our body shape is morphing in ways we don't like. Sometimes they try to give us straight talk, pushing our cholesterol a little higher or we have IBS or indigestion. At other times they're screaming, we're pre-diabetic or full blown, our moods are a mess, and our immune systems confused and attacking us. Every one of these health signals hides a specific kind of metabolic dysfunction, and for each, food is the answer. In her new book, Haylie teaches us that anyone can achieve the body and health they want from the foods that they choose and use"--